The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1093/nar/26.11.2572
|View full text |Cite
|
Sign up to set email alerts
|

SCP2: a major protein component of the axial elements of synaptonemal complexes of the rat

Abstract: In the axial elements of synaptonemal complexes (SCs) of the rat, major protein components have been identified, with relative electrophoretic mobilities (M rs) of 30 000-33 000 and 190 000. Using monoclonal anti-SC antibodies, we isolated cDNA fragments which encode the 190 000 M r component of rat SCs. The translation product predicted from the nucleotide sequence of the cDNA, called SCP2 (for synaptonemal complex protein 2), is a basic protein (pI = 8.0) with a molecular mass of 173 kDa. At the C-terminus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
159
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(166 citation statements)
references
References 67 publications
4
159
0
1
Order By: Relevance
“…During embryogenesis, all SYCP family members are expressed specifically in the nucleus of meiotic prophase I cells (spermatocytes in males and oocytes in females). SYCP3 appears first at the leptotene stage, and subsequently SYCP1 and SYCP2 appear at the zygotene and pachytene stages respectively (Meuwissen et al 1992, Lammers et al 1994, Offenberg et al 1998, Yuan et al 2000, but pre-meiotic cells (spermatogonia in males and oogonia in females) do not contain detectable amounts of SYCP mRNA. After sexual maturation, expression of mammalian SYCP family members is specific to testis and restricted to meiotic prophase I spermatocytes (Offenberg et al 1998, Yang et al 2006.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During embryogenesis, all SYCP family members are expressed specifically in the nucleus of meiotic prophase I cells (spermatocytes in males and oocytes in females). SYCP3 appears first at the leptotene stage, and subsequently SYCP1 and SYCP2 appear at the zygotene and pachytene stages respectively (Meuwissen et al 1992, Lammers et al 1994, Offenberg et al 1998, Yuan et al 2000, but pre-meiotic cells (spermatogonia in males and oogonia in females) do not contain detectable amounts of SYCP mRNA. After sexual maturation, expression of mammalian SYCP family members is specific to testis and restricted to meiotic prophase I spermatocytes (Offenberg et al 1998, Yang et al 2006.…”
Section: Discussionmentioning
confidence: 99%
“…A third longitudinal structure, the central element, is located on the TFs between both LEs of SCs (Lammers et al 1994, Meuwissen et al 1997. Three isoforms of SC proteins (SYCPs), SYCP1, SYCP2 and SYCP3 (also known as SCP1, SCP2 and SCP3), have been identified in mammals as structural component proteins in SCs (Meuwissen et al 1992, Lammers et al 1994, Offenberg et al 1998). SYCP1 is the major component of the TFs of SCs, whereas SYCP2 and SYCP3 have been identified in the LEs .…”
Section: Introductionmentioning
confidence: 99%
“…The extension and position of coiled coil domains, which were predicted by the Lupas algorithm, are represented by the light blue boxes. The diagram is adopted from SYCP2 and SYCP3 are the major constituents of the LEs (Lammers et al 1994;Offenberg et al 1998). Both proteins assemble along the chromosome axes in leptotene and remain localized in the AEs/LEs until diplotene .…”
Section: -2)mentioning
confidence: 99%
“…Immunolabeling of SC proteins has indicated that most of the structural modifications shown by the unsynapsed AEs of sex chromosomes correlate with a differential deposition of SYCP2 and SYCP3 proteins, that are the main components of the AEs/LEs in mammals (Lammers et al 1994;Dobson et al 1994;Moens and Spyropoulos 1995;Offenberg et al 1998). Moreover, SYCP1, the main component of TFs and the CE (Meuwissen et al 1992), may also contribute to these modifications.…”
Section: Sex Chromosomal Aes Are Highly Modified In Eutherian Mammalsmentioning
confidence: 99%